The Effects of Thermal Pre-Treatment on the Electrical Conductivities of Rutile and Zircon - Hayes P. C (The Australasian Institute of Mining and Metallurgy, 1991)
In commercial mineral processing operations it has been found that the conditions in the drier have a considerable effect on the subsequent electrostatic separation of nttile and zircon. Laboratory scale studies simulating these heat treatment processes have shown that the electrical conductivity of nitile varies markedly with treatment temperature, time and gas composition. The zircon on the other hand is unaffected. By increasing the electrical conductivity of the rutile, significant increases in separation efficiency can be achieved. Electron microscope investigations have shown the increase in electrical conductivity to be associated with the production of planar defects in the crystal lattice.